Inside the “Hybrid” Iron Cage: Political Origins of Hybridization - Kim, Tai-Young; Shin, Dongyoub; Jeong, Young-Chul (Organization Science, 2016)
This paper examines how social-movement-type political interactions between conflicting parties within an organization influence the adoption of a hybrid practice. We argue that a hybrid practice is likely to be adopted when power balance between challengers and incumbents is achieved. To shed light on conditions for organizational settlement based on such power balance, we focus on three factors: structures, actors, and processes of social-movement-type political interactions within organizations. By studying changes in the presidential selection systems of Korean universities between 1988 and 2006, this paper illustrates how organizational settlement resulted in the adoption of a hybrid system by combining elements of two previous competing presidential selection systems—appointment and direct voting systems. The general implications for the understanding of hybridization, organizational settlement, and organizational heterogeneity are discussed.